2000
DOI: 10.1212/wnl.54.4.927
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid HIV RNA originates from both local CNS and systemic sources

Abstract: CSF and plasma HIV dynamics became increasingly independent in advanced HIV disease, and the compartmental discrepancy was largest in HAD. Our findings suggest that viral replication in CNS tissues may constitute a major, independent source of CSF HIV RNA. In patients with HAD, brain parenchyma itself may be the principal CNS tissue source, and CNS-targeted treatment strategies may be required to eradicate this infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(145 citation statements)
references
References 42 publications
12
130
0
3
Order By: Relevance
“…[57, 58]) substantially slower, likely depending on the main source of the virus: T-tropic CSF HIV predominating in earlier infection decays quickly, in parallel with plasma, while M-tropic CSF HIV found more commonly late in infection, particularly in HAD in which infected macrophages play a central role, decays more slowly. This likely relates to the different longevities of the cells supporting infection, short for T lymphocytes and longer for macrophages, and to different replication modalities within the two cell types [7,24,[34][35][36][37]. This also may have implications for the demands of ART in suppressing CNS infections in the two settings: when derived and constantly renewed by systemic infection, systemically effective treatments may be fully capable of reducing CNS infection in parallel.…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 99%
“…[57, 58]) substantially slower, likely depending on the main source of the virus: T-tropic CSF HIV predominating in earlier infection decays quickly, in parallel with plasma, while M-tropic CSF HIV found more commonly late in infection, particularly in HAD in which infected macrophages play a central role, decays more slowly. This likely relates to the different longevities of the cells supporting infection, short for T lymphocytes and longer for macrophages, and to different replication modalities within the two cell types [7,24,[34][35][36][37]. This also may have implications for the demands of ART in suppressing CNS infections in the two settings: when derived and constantly renewed by systemic infection, systemically effective treatments may be fully capable of reducing CNS infection in parallel.…”
Section: Cns Hiv Infection and Treatment Effectsmentioning
confidence: 99%
“…[124][125][126][127] Nevertheless commercial kits for measuring HIV RNA have not been validated in the CSF and the threshold is currently unknown. Second generation methods can quantify as low as 20 copies/mL; very sensitive experimental techniques (quantifying 2 copies/mL) have been assessed and residual viremia (between 2 and 50 copies/mL) was associated with worse cognitive function.…”
Section: Target Concentrationsmentioning
confidence: 99%
“…Slower decay of CSF HIV RNA has been noted in subjects with HAD and lower CD4 cell counts. [125,126,154,155] Ninety percent of patients with undetectable plasma HIV RNA presented CSF HIV RNA below 50 copies/mL: nevertheless a compartmental residual viremia was measurable through sensitive methods. CSF low-level viremia was associated with neurocognitive impairment, with increased immune activation and it was unresponsive to intensification strategies (with maraviroc, enfuvirtide or raltegravir).…”
Section: Efficacy Of Monotherapy Versus Combination Antiretroviral Trmentioning
confidence: 99%
“…In addition, several studies have conclusively shown that HAART can suppress cerebral spinal fluid (CSF) levels of HIV ribonucleic acid (RNA) (Foudraine et al, 1998) and this decline appeared to correlate with the successful reversal of neurological deficit (Ellis et al, 2000;Marra, 1999). However, despite the progress associated with HAART, HIVassociated neurological disease continues to be the major cause of morbidity and mortality in HIV patients, suggesting that HAART does not provide complete protection against neurological damage in HIV/AIDS (Dougherty et al, 2002;Kolson, 2002;Sacktor et al, 2001a).…”
Section: Introductionmentioning
confidence: 99%